FOSTERING TRIPARTITE PARTNERSHIPS IN SOUTH AFRICA: THE CRITICAL ROLE OF COLLABORATIVE PARTNERSHIPS BETWEEN SOCIAL WORK TRAINING INSTITUTIONS AND PUBLIC-PRIVATE WELFARE SECTORS - Masinga, Poppy; Engelbrecht, Lambert K (Social Work/Maatskaplike Werk, 2024)
The necessity of collaboration and partnership among key stakeholders in advancing the social work profession in South Africa is evident. Accordingly, the development of formal communication structures between social work training institutions and public-private welfare sectors is strongly encouraged. Initiatives such as joint task teams, working groups, or advisory committees should be established to facilitate streamlined collaboration and partnerships, thereby enhancing the design and delivery of social service programmes. The collaboration of all three key stakeholders is crucial to establishing an effective and efficient social welfare and social work system that responds appropriately to the contextual needs of South Africa. Strengthening and fostering the proposed tripartite collaboration is indispensable for advancing social work research and education, shaping and analysing social policy, and improving social work practice to maximise its societal impact.